2009
DOI: 10.1177/0961203309345778
|View full text |Cite
|
Sign up to set email alerts
|

Premature coronary artery calcification is associated with disease duration and bone mineral density in young female systemic lupus erythematosus patients

Abstract: Our objective was to evaluate the relevance of traditional and disease-related cardiovascular risk factors and of bone mineral density for premature coronary artery calcification in young patients with systemic lupus erythematosus. Ninety-four female patients with systemic lupus erythematosus with disease durations >5 years and <45 years were consecutively selected. Cardiovascular risks (diabetes mellitus, arterial hypertension, dyslipoproteinemia, smoking, family history, body mass index, ovarian and renal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 53 publications
(74 reference statements)
1
7
1
1
Order By: Relevance
“…In addition, hypogammaglobulinemia has been reported in approximately half of renal transplant patients receiving MMF in combination with CS [8]. It is of interest to note that an increased risk of infection has been observed in other LN studies during the induction phase with MMF and high-dose CS, compared with the maintenance phase [9,10]. The results reported here raise the possibility that this increased risk may be associated with severe hypogammaglobulinemia.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, hypogammaglobulinemia has been reported in approximately half of renal transplant patients receiving MMF in combination with CS [8]. It is of interest to note that an increased risk of infection has been observed in other LN studies during the induction phase with MMF and high-dose CS, compared with the maintenance phase [9,10]. The results reported here raise the possibility that this increased risk may be associated with severe hypogammaglobulinemia.…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand, women with cardiovascular disease have increased risk of osteoporotic fracture [ 28 ]. In patients with SLE, decreased BMD is an independent predictor for premature coronary calcification [ 29 ]. The definite link between atherosclerosis and osteoporosis suggested that they may share common risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment failure was defined by one of the following components: renal flare, sustained doubling of serum creatinine, initiation of rescue therapy for nephritis, end stage renal disease, or death. The cumulative incidence of treatment failure at 36 months was 16% in MMF group vs. 32% in the azathioprine group [32]. This difference was consistent among all racial groups.…”
Section: Mycophenolate Mofetilmentioning
confidence: 84%